CLARY SAGE YIELD AND ESSENTIAL OIL OUTPUT DEPENDING ON THE STUDIED AGRO–TECHNICAL FACTORS - Ushkarenko, V. O.; Vozhehova R. А.; Kokovikhin, S. V.; Shepel, A. V.; Chaban, V. O. (Scientific Progress & Innovations, 2020)
The article analyzes the state of clary sage cultivation in Ukraine, application of muscat plant raw mate-rials of guaranteed quality, as well as the principles and rules of good practices for the production of herbal medicines in accordance with GMP (Good Manufacturing Practices, or proper manufacturing practices), which reflect standardization requirements to muscat plant raw materials and the main indicators of their quality.. Using BK–1.0 instead of KPS–4 harrow–cultivator for pre–sowing soil tillage resulted in increasing pre–sowing soil moisture in a layer of 0–30 cm in all studied variants. Sowing time also affected crop productivity. The maximum yield of clary sage inflorescences in the first, second and third years of using was obtained during the first (first decade of December) sowing period – 14.61–15.01 t/ha at N60P90 fertilization. . The optimal dose of mineral fertilizers at plowing was determined. The optimal sowing time of clary sage, the width of row–spacing, and also the appropriate terms for using the plantation were determined. It was found that when the air temperature increased to 40 °C (mowing period from 1 to 4 o’clock p.m.), the con-tent of essential oil in inflorescences was minimal among all experimental variants and amounted to 0.05% against the natural nutrition background and 0.25 % under N60P90 fertilization. Harvesting from 4 p.m. to 7 p.m. and also from 7 p.m. to 10 p.m. increases the content of essential oil in clary sage inflorescences as compared with hotter hours of the day, but does not reach the indicators of early harvesting hours from 6 a.m. to 11 a.m. The maximum crop productivity in the variants of different plowing depths of 20–22 and 28–30 cm was obtained during the first (first decade of December) sowing period – 50.58 and 53.80 kg/ha per year, respectively. The postponement of the crop sowing time to the spring led to a significant decrease in clary sage productivity. So, when sowing in the second decade of March, clary sage productivity de-creased 42.3 %, on the average for the variants of different plowing depths, when sowing in the third decade of March – by 118.2 % as compared with the first sowing period. The minimum amount of conditionally col-lected clary sage essential oil – 19.36 kg/ha was obtained at sowing in the last spring period – the first dec-ade of April. Thus, the best time for sowing clary sage, at which the maximum conditional collection of the crop essential oil was obtained – 50.58–53.80 kg/ha per year, turned out to be the first – winter period, which was conducted in the first decade of December.